Pengukuran Tingkat Kepentingan Pelanggan Food Court Galaxy Mall Surabaya dengan Metode Kano Model - Rahardjo, Benedictus; Limantara, Yosafat Cahaya Putra; Cahyono, Tania Nano; Anthoni, Robert Yunior (Universitas Suryakancana, 2018)
Abstract— The research conducted focuses on the services provided by Galaxy Mall Surabaya regarding the food court. Food court is a place for customers to buy food in addition to the existing food stores, so the food court has an important role in the economy of a mall. The study was conducted to find out what things are considered important and must be in a food court, especially in Galaxy Mall Surabaya. This is gained through functional and dysfunctional questions. The study was conducted by distributing an online questionnaire. Questionnaires are distributed to 100 respondents from various backgrounds and know the food court of Galaxy Mall or have used the facility. The results obtained show that the factors asked have been applied by the Galaxy Mall well. The results of data recaps performed show that functional and dysfunctional questions on Kano Model produce indifferent result. These results are obtained in all functional and dysfunctional questions. Therefore, Galaxy Mall is able to apply the services that are important only in the management of his food court.Keywords: Importance Measurement; Service Quality; Kano Model; Indifferent